National-Subnational Coordination for Investment Attraction : The Case of Spain - Fernandez, María Jesus (World Bank, Washington, DC, 2021)
This paper is part of the broader World Bank Group (WBG) research initiative on Investment Climate matters, managed by the Finance, Competitiveness and Innovation (FCI) Global Practice of the WBG. Its objective is to create a knowledge base in the investment policy and promotion arena to help governments address questions on effective policies, by understanding what has worked elsewhere and what has not, and on how to organize for delivery in different contexts. This paper has three objectives: First, to understand better the rationale behind having national and subnational IPAs. Second, to shed light on how national and subnational IPAs can cooperate to attract FDI. And third, to take a closer look at specific mechanisms that can generate significant synergies, benefits and opportunities for the host economies. In all cases this note draws on the example of the collaboration between the different Spanish national and regional administrations, a successful model showing how coordination efforts result in an improvement of the efficiency and effectiveness of overall investment policy and promotion efforts.